Observation of Immediate and Short Term Results of Percutaneous Trans-Catheter Device Closure of Atrial Septal Defect in a Paediatric Cardiac Centre, Bangladesh (The Planet, 2024)
Introduction: Atrial Septal Defect (ASD) is a common congenital heart defect that can lead to various complications if left untreated. Percutaneous trans-catheter device closure has emerged as a viable alternative to surgical closure, especially for secundum ASDs. However, data on its effectiveness and safety in a resource-constrained setting like Bangladesh are limited. Methods and materials: This prospective observational study was conducted at Pediatric Cardiac Centre, Combined Military Hospital Dhaka, a tertiary care center in Bangladesh. Fifty patients with secundum ASD were enrolled and underwent percutaneous trans-catheter ASD device closure. Various parameters like age, gender, comorbidities, presenting symptoms, and investigation findings were analyzed. Immediate and short-term outcomes following intervention were assessed through clinical examination and follow-up investigations. Result: The device was successfully implanted in 48 out of 50 patients (96%). No residual shunts were observed in any of the successful cases during the follow-up period. Right Ventricular (RV) size normalization was observed in 81.25% of the patients by the third follow-up. Incomplete Right Bundle Branch Block (RBBB) with or without Right Ventricular Hypertrophy (RVH) decreased from 66.67% immediately post-procedure to 35.42% at the third follow-up. Conclusion: The study confirms the safety and efficacy of percutaneous trans-catheter ASD device closure in a resource-constrained setting. It also emphasizes the importance of thorough pre-procedure evaluation for optimal patient selection and outcome.
Keywords: Atrial Septal Defect; Percutaneous Trans-Catheter Device Closure; Resource-Constrained Setting; Safety; Efficacy